Postplacental IUCD CuT380A: Acceptability, Effectivity and Side Effects - Situmorang, Herbert; Setijanto, Ivanna T; Affandi, Biran (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To evaluate the acceptability, effectivity and side effects of Postplacental IUCD after vaginal delivery at Dr. Cipto Mangunkusumo Hospital (RSCM) after 6 month of insertion. Methods: A prospective study was conducted at RSCM Jakarta during the period of August to October 2012. Postplacental IUCD was inserted into the subjects’ uterus until it reached the fundus. Follow up was done at 40-42 days and 6 months after delivery.  Results: A total of 234 women were recruited in this study, with 19.2% loss of follow up. No significant difference on subjects characteristics who came and loss of follow up in this study. Expulsion was experienced by 5.1% subjects (total expulsion 4.1% and partial 1%) at the first visit on 40-42 days and 7.5% subjects (total expulsion 0.6% and partial 6.9%) at the second visit, after 6 months. 9.3% subjects had the IUCD removed at the first and second visit. Among all of the subjects who had the IUCD removed by request or had the expulsion, 61% were willing to do reinsertion. The effectivity of IUCD was 100%, with 68.9% subjects was still breastfeeding. The side effects were vaginal discharge (23%), dysmenorrhea (4-21%), and spotting (2-10%).  Conclusion: The acceptability and effectivity of postplacental IUCD after 6 months were 86.8% and 100%. Cummulative expulsion rate were 12.6%, and the most common side effects were vaginal discharge, dysmenorea, and spotting. Keywords: acceptability, effectivity, expulsion rate, IUD, postplacenta